Oportunidades e desafios decorrentes da inserção da indústria 4.0: um estudo sobre a transformação digital no setor de eletroeletrônicos no PIM - Rocha, Pollyana Masulo (Brasil, 2025)
This study aims to investigate the implementation of industry 4.0 in the Manaus Industrial Pole, with the aim of identifying the main challenges and opportunities faced by electronics companies, and how these factors influence production efficiency, supply chain optimization and creation of new business models, making companies more competitive. Using a quantitative approach, the research explores the challenges and opportunities faced by managers during the transition to advanced technologies, such as the Internet of Things (IOT), big data, automation and artificial intelligence. Data collection was carried out using the PIMM 4.0 system where a structured questionnaire was created, developed based on a comprehensive review of the existing literature on Industry 4.0. The results highlight the main barriers and facilitators in the adoption of these technologies, providing an overview of current practices and proposing strategies to maximize the benefits of the new industry in the industrial context of the capital. The analysis suggests that integrated strategies that include ongoing training and skills development programs are essential. Furthermore, exemplary and innovative practices.